Looking for Lost Bird : a Jewish woman's discovery of her Navajo roots - Melanson, Yvette D.; Safran, Claire (New York : Bard, 2000)
"In this haunting memoir, Yvette Melanson tells of being raised to believe that she was white and Jewish. At age forty-three, she learned that she was 'Lost Bird, ' a Navajo child taken against her family's wishes, and that her grieving birth mother had never stopped looking for her until the day she died."
"An Avon book."
Keywords: Melanson, Yvette D; Navajo women -- Arizona -- Tolani Lakes Region -- Biography; Jewish women -- New York (State) -- Neponsit (New York) -- Biography; Adoptees -- New York (State) -- Neponsit (New York) -- Biography; Navajo Indians -- Arizona -- Tolani Lakes Region -- Social life and customs